Triple Therapy-Based on Tegoprazan, a New Potassium-Competitive Acid Blocker, for First-Line Treatment of Helicobacter pylori Infection: A Randomized, Double-Blind, Phase III, Clinical Trial - Choi, Yoon Jin; Lee, Yong Chan; Kim, Jung Mogg; Kim, Jin Il; Moon, Jeong Seop; Lim, Yun Jeong; Baik, Gwang Ho; Son, Byoung Kwan; Lee, Hang Lak; Kim, Kyoung Oh; Kim, Nayoung; Ko, Kwang Hyun; et al. (Gut and liver, 2022)
We examined the efficacy and safety of tegoprazan as a part of first-line triple therapy for Helicobacter pylori eradication.Background/AimsWe examined the efficacy and safety of tegoprazan as a part of first-line triple therapy for Helicobacter pylori eradication.A randomized, double-blind, controlled, multicenter study was performed to evaluate whether tegoprazan (50 mg)-based triple therapy (TPZ) was noninferior to lansoprazole (30 mg)- based triple therapy (LPZ) (with amoxicillin 1 g and clarithromycin 500 mg; all administered twice daily for 7 days) for treating H. pylori. The primary endpoint was the H. pylori eradication rate. Subgroup analyses were performed according to the cytochrome P450 (CYP) 2C19 genotype, the minimum inhibitory concentration (MIC) of amoxicillin and clarithromycin, and underlying gastric diseases.MethodsA randomized, double-blind, controlled, multicenter study was performed to evaluate whether tegoprazan (50 mg)-based triple therapy (TPZ) was noninferior to lansoprazole (30 mg)- based triple therapy (LPZ) (with amoxicillin 1 g and clarithromycin 500 mg; all administered twice daily for 7 days) for treating H. pylori. The primary endpoint was the H. pylori eradication rate. Subgroup analyses were performed according to the cytochrome P450 (CYP) 2C19 genotype, the minimum inhibitory concentration (MIC) of amoxicillin and clarithromycin, and underlying gastric diseases.In total, 350 H. pylori-positive patients were randomly allocated to the TPZ or LPZ group. The H. pylori eradication rates in the TPZ and LPZ groups were 62.86% (110/175) and 60.57% (106/175) in an intention-to-treat analysis and 69.33% (104/150) and 67.33% (101/150) in a per-protocol analysis (non-inferiority test, p=0.009 and p=0.013), respectively. Subgroup analyses according to MICs or CYP2C19 did not show remarkable differences in eradication rate. Both first-line triple therapies were well-tolerated with no notable differences.ResultsIn total, 350 H. pylori-positive patients were randomly allocated to the TPZ or LPZ group. The H. pylori eradication rates in the TPZ and LPZ groups were 62.86% (110/175) and 60.57% (106/175) in an intention-to-treat analysis and 69.33% (104/150) and 67.33% (101/150) in a per-protocol analysis (non-inferiority test, p=0.009 and p=0.013), respectively. Subgroup analyses according to MICs or CYP2C19 did not show remarkable differences in eradication rate. Both first-line triple therapies were well-tolerated with no notable differences.TPZ is as effective as proton pump inhibitor-based triple therapy and is as safe as first-line H. pylori eradication therapy but does not overcome the clarithromycin resistance of H. pylori in Korea (ClinicalTrials.gov identifier NCT03317223).ConclusionsTPZ is as effective as proton pump inhibitor-based triple therapy and is as safe as first-line H. pylori eradication therapy but does not overcome the clarithromycin resistance of H. pylori in Korea (ClinicalTrials.gov identifier NCT03317223).